Electric Field-Assisted In Situ Precise Deposition of Electrospun γ-Fe(2)O(3)/Polyurethane Nanofibers for Magnetic Hyperthermia - Song, Chao (Nanoscale Res Lett, 2018)
A facial electrospinning method of in situ precise fabricating magnetic fibrous membrane composed of polyurethane (PU) nanofibers decorated with superparamagnetic γ-Fe(2)O(3) nanoparticles with simultaneous heat generation in response to alternating magnetic field (AMF) is reported. In this method, a conical aluminum auxiliary electrode is used to regulate the electrostatic field and affect the process of electrospinning for the in situ rapid and precise deposition of electrospun γ-Fe(2)O(3)/PU fibers. The auxiliary conical electrode can extend the jet stabilization zone of the precursor solution four times longer than that of without auxiliary electrode, which can achieve the precise control of the fiber deposition area. Moreover, the electrospun composite fibrous membranes show a rapid temperature increase from room temperature to 43 °C in 70 s under the AMF, which exhibits faster heating rate and higher heating temperature compared to the samples fabricated without the assist of the auxiliary electrode. The present results demonstrate that the in situ precise electrospinning with the help of an auxiliary conical electrode has the potential as a manipulative method for preparing magnetic composite fibers as well as magnetic hyperthermia of cancer therapy.